In silico, in vitro, and in vivo antidiabetic activity of an alkaloid, 1, 2-dimethoxy-12-methyl-7-(3-methylbut-2-en-1-yl)-12, 13-dihydro [1,3] benzodioxolo [5,6-c] phenanthridin-13-ol, isolated from a Zimbabwean herbal antidiabetic medicine - Dzomba, Pamhidzai; Mugari, Pardon; Nyoni, Stephen; Mudewairi, Elias (John Wiley & Sons Ltd., 2026)
Protein tyrosine phosphatase 1B (PTP1B) is a crucial drug target for treating diabetes mellitus Type 2 (DMT2) because of its link to insulin resistance. Currently there are no approved clinical drugs targeting PTP1B. Therefore, the present study was aimed at investigating the mode of action of an alkaloid, 1, 2-dimethoxy-12-methyl-7-(3-methylbut-2-en-1-yl)-12, 13-dihydro [1,3] benzodioxolo [5,6-c] phenanthridin-13-ol (1, 2 DMMDBP), previously isolated from a popular Zimbabwean antidiabetic herbal medicine. Molecular docking studies using PDB, 2QBP (catalytic site) and IT48 (allosteric site), in vitro PTP1B enzyme inhibition, and in vivo assays using streptozotocin induced diabetic rats were applied to investigate antidiabetic effect. Drug-like and toxicity properties were evaluated using SwissADME and Protox 3.0 webservers, respectively. Molecular docking results showed that the test compound (1, 2 DMMDBP) has a greater binding affinity (11.1 kcal/mol, rmsd, 0.000 Å) for the allosteric site than the catalytic site (9.6 kcal/mol, rmsd, 0.000 Å). In vitro inhibition assay showed that 1, 2 DMMDBP was more potent (IC50 = 1.10 _M ) than that of ursolic acid (IC50 = 7.13 _M). Additionally, in in vivo studies, 1, 2 DMMDBP maintained normal hypoglycemia and mass better than the reference drug metformin. In absorption, distribution, metabolism, and excretion predictive studies, 1, 2 DMMDBP showed good drug-like properties. It did not violate any of Lipinski's classic rules. It showed good physicochemical properties such as absorption, (log of skin permeability (log Kp) value was −4.95), bioavailability with a core of 0.55 and biotransformation by cytochrome-P enzymes CYP1A2 and CYP3A4. Protox 3.0 webserver predicted LD50 value of 1000 mg/kg, showing that it may be toxic if swallowed. Based on the evidence presented, 1, 2 DMMDBP is a highly promising compound in the development of potent and selective allosteric modulator drugs of PTP1B for the treatment of DMT2 upon further studies.
Keywords: Protein tyrosine phosphatase 1B; Molecular docking; Diabetes mellitus Type 2; 1; 2-dimethoxy-12-methyl-7-(3-methylbut-2-en-1-yl)-12; 13-dihydro [1; 3] benzodioxolo [5; 6-c] phenanthridin-13-ol